Real-time assay of inorganic pyrophosphatase activity in the red region based on Li+-doped NaYF4:Yb, Er upconversion luminescent nanoparticles. Issue 22 (26th May 2017) - Wang, Lei; Ji, Yuan; He, Yuezhen; Wang, Lun; Chen, Hongqi
Abstract : Based on a competition assay approach, a new highly sensitive method for real-time detection of PPase activity using Li + -doped NaYF4 :Yb, Er upconversion red luminescent nanoparticles was developed. Abstract : Li + -Doped NaYF4 :Yb, Er upconversion luminescent nanoparticles (UCLNPs) were synthesized and modified with poly(acrylic acid) (PAA). The luminescence of the carboxyl-functionalized UCLNPs at 664 nm was quenched in the presence of cupric ions (Cu 2+ ) due to the coordination of Cu 2+ with the carboxyl group of PAA. When pyrophosphate ions (PPi) were added, the luminescence of the UCLNPs was restored due to the competitive binding of PPi with Cu 2+ . However, pyrophosphatase (PPase) could promote the hydrolysis of PPi, thus releasing Cu 2+, leading to requenching of the luminescence. Under optimal conditions, the luminescence response was virtually proportional to the activity of the PPase between 0.500 and 50.0 mU mL −1, and the limit of detection was 0.441 mU mL −1 . Based on the competition assay approach, a new highly sensitive method in the red region for real-time detection of PPase activity was developed.